IMPACT OF SUBSTRUCTURAL COMPOSITION ON THE FIDELITY AND DIGITIZATION EFFICIENCY OF IMPLANT-SUPPORTED FULL-ARCH FRAMEWORK SUBSTRUCTURES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Within the digital workflow for full-arch implant-supported fixed restorations, the bar substructure serves as a foundational element upon which aesthetic suprastructures are cemented. In certain clinical scenarios, intraoral digitization of these substructures is necessary; however, the scanning performance and dimensional reliability of different bar materials remain incompletely characterized (Rutkunas et al., 2021). This study aimed to evaluate and compare the scanning efficiency and accuracy of two materials used in implant-supported bar frameworks: titanium and polyetheretherketone (PEEK).A maxillary edentulous patient with four integrated implants received two identical bar substructures milled via CAD/CAM—one from titanium and one from PEEK. Each substructure was digitized using a laboratory-grade desktop scanner to produce a reference stereolithography (STL) file. Subsequently, each bar underwent ten intraoral scans using a standardized protocol with a defined time constraint.
Keywords: Scanning accuracy, digitization efficiency, PEEK, titanium, implant-supported prosthesis, trueness, precision, intraoral scanning.